Analisa Putusan Bebas Oleh Hakim Terhadap Pelaku Tindak Pidana Korupsi (Studi Kasus Putusan Mahkamah Agung Nomor 2298 K/Pid.Sus/2019). - Jelita, Tetty; Sujatno, Adi (Neolectura, 2024)
One of the diseases that continues to afflict Indonesia is corruption, perpetrated by various groups, including the legislative, executive, law enforcement, and bureaucratic sectors, from the central government down to the regional and village levels. Corruption is considered an extraordinary crime due to its massive impact in both the short and long term. Not only does it harm the state, but it also brings suffering to the people. The formulation in this research is: how is the application of criminal sanctions against perpetrators of corruption crimes? And how does the judge's reasoning lead to an acquittal in the Supreme Court decision number 2298 K/Pid.Sus/2019 on a corruption case? The research method used is a normative juridical approach. The normative juridical approach is a method based on primary legal materials by examining theories, concepts, legal principles, and regulations related to this research. The findings of this study reveal that criminal law governing corruption crimes is derived from special criminal law, namely Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 on the Eradication of Corruption. The types of criminal penalties that judges can impose on perpetrators of corruption crimes include the death penalty if committed under